2017
DOI: 10.18632/oncotarget.14817
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations of gastrokine 1 gene expression in gastric cancer

Abstract: The gastrokine 1 (GKN1) protein is important for maintaining the physiological function of the gastric mucosa. GKN1 is down-regulated in gastric tumor tissues and derived cell lines and its over-expression in gastric cancer cells induces apoptosis, suggesting a possible role for the protein as a tumor suppressor. However, the mechanism by which GKN1 is inactivated in gastric cancer remains unknown. Here, we investigated the causes of GKN1 silencing to determine if epigenetic mechanisms such as histonic modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…We also identified a downstream target of KRAS (MUC16) as DEG, supporting KRAS implications in survival 33 . Also, we observed modifications of GKN1, KRT6, and ANKRD43 gene expressions in LTS, known to induce apoptosis and metastasis cancer 34,35 . A previous study showed REG4 as a serological marker for PDAC 36 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We also identified a downstream target of KRAS (MUC16) as DEG, supporting KRAS implications in survival 33 . Also, we observed modifications of GKN1, KRT6, and ANKRD43 gene expressions in LTS, known to induce apoptosis and metastasis cancer 34,35 . A previous study showed REG4 as a serological marker for PDAC 36 .…”
Section: Discussionmentioning
confidence: 71%
“…To analyses the effect of perturbed genes in PEEPs (gene is significantly perturbed or not) in LT survivor's heterogeneity, two-way clustering (biclustering) highlighted 64 gene clusters (appendix pp [33][34]. The largest cluster (cluster 15) consisted of 363 genes.…”
Section: Biclustering Of Functional Profilesmentioning
confidence: 99%
“…As already reported [7], for the Chip assay it was identified a 600 bp GKN1 promoter region that was divided into three segments of about 160 bp (A, B, and C). Compared with non-tumoral tissues, ChIP assays performed on these segments did not reveal a significant association of RUNX3 in tumoral tissues.…”
Section: Gkn1 Down-regulation In Gc Is Not Associated With Runx3 On Tmentioning
confidence: 70%
“…In fact, chromatin immunoprecipitation assays for the trimethylation of histone 3 at lysine 9 (H3K9triMe) and its specific histone-lysine N-methyltransferase (SUV39H1), performed on human specimens of normal and cancerous gastric tissues, showed that GKN1 down-regulation in GC tissues was associated with high levels of H3K9triMe and with the recruitment of SUV39H1 to the GKN1 promoter. These findings suggested that an epigenetic transcriptional complex could negatively regulate GKN1 expression in gastric tumors [7].…”
mentioning
confidence: 89%
See 1 more Smart Citation